Classic Yugoslav literatures as expressing of the salient elements and issues of Yugoslavian society, 9.6. 1987. Smithsonian Institute, Washington - Gjurgjan, Ljiljana Ina (1987)
The lecture ahs concentrated on the case of Croatia and its complex tradition with its three scripts and three dialects and has outlined the influence of folk tradition which made its Renaissance poetry different from the Italian. The four baroque centres and the differences in their poetics have also been outlined.
ENG